Sectoral FDI and the real exchange rate: The role of financial development - Coletta Frenzel Baudisch (Philipps-University Marburg, School of Business and Economics, 2018)
Increasing FDI inflows into a booming sector resulting in an appreciation of the real exchange rate may entail further capital inflows and greater appreciation pressure on the real exchange rate up to an abrupt reversal of the capital (Botta, 2015). The macroeconomic instability of such boom-and-bust cycles is detrimental to economic growth, as is the appreciated real exchange rate. This paper applies dynamic system generalized methods of moments (GMM) estimation techniques to empirically find different effects of foreign direct investment (FDI) inflows into the main economic sectors on the real exchange rate in a panel of 66 developing and developed economies. While the effect of FDI in the primary sector appears to be insignificant, FDI in the manufacturing and in the service sector lead to a real depreciation and a real appreciation respectively. Furthermore, evidence suggests that financial sector development may help in dampening the real exchange rate movements induced by FDI in the latter two sectors, as well as distinctly attenuates the real appreciation effect of other capital inflows. Hence, deep financial markets seem to contribute to the mitigation of macroeconomic instability in consequence of capital inflows.
Keywords: C33; E44; F21; F32; 330; Capital Inflows; Sectoral Foreign Direct Investment; Financial Market Development; Dynamic Panel Data Models